Global Tax Risk of Imports: Is Royalty Payment Included in Customs Import Valuation? - Ming, Lau Chung (Archives of Business Research, 2024)
Prompted by the need to expand to overseas market, numerous multinational companies (MNCs) engage in import and export. From the perspective of global tax, one significant tax risk regarding customs duty is considered as neglected. In recent years, several evidence has shown the necessary concerns in relation to customs duty. This study empirically examines the current legislations and latest trends of enforcement and valuation of import customs in major countries or regions, especially as they relate to the payment of royalties from overseas affiliates of MNCs to the headquarters. A single-case study was adopted to investigate and elaborate the issues associated with import custom practice of a typical Japanese MNCs. The findings indicate that the persons in charge or management seniors, besides the department of custom declaration, did not alert of or recognize any tax risks of royalty payment influencing import custom valuation and calculation. Relevant insights and recommendations are enumerated for future reference by other MNCs.